RE-ORIENTASI PENDIDIKAN ISLAM PERSPEKTIF MUHAMMAD ABDUH DAN RELEVANSINYA DI LEMBAGA PENDIDIKAN ISLAM MADURA - ANDRI SUTRISNO (Balai Diklat Keagamaan Palembang, 2022)
Muhammad Abduh was one of the Muslim intellectuals in the modern century who carried out the renewal of Islam in all scientific fields by promoting the approach of rationalism. Especially in the field of renewal of Islamic education. Madura is one of the islands in Nasantara that has Islamic educational institutions that are very concerned about the niali-nilai teachings contained in Islam. With this, the author wants to understand about the concept of Islamic education in the view of muhammad abduh and its relevance in Islamic educational institutions in Madura. So that this research is included in descriptive qualitative research that combines literature studies. As for data collection techniques, the author will use four techniques, namely interviews, observations, documentation and libraries. Sedagkan data analysis using content analysis. In the study it was found that muhammad abduh was born in thanta in 1849, islamic education according to him was divided into two parts of reason education and spritual education. As well as the method of applying Islamic education and its relevance in Madura Islamic educational institutions, it is carried out in two methods, namely the method of school management system and teaching system.